2018
DOI: 10.4025/actasciagron.v41i1.39497
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in popcorn synthetic population

Abstract: The Brazilian popcorn has low genetic variability and the successful development of advanced lines, new popcorn cultivars with high grain yield (GY) and expansion volume (PE) is dependent on parental selection and precise determination of heterotic groups. The aim of this study was to evaluate genetic variability and identify heterotic groups in synthetic populations of popcorn, using diallel crosses. Thus, nine synthetic populations were crossed using complete diallel scheme. The GY and PE traits of 36 hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…In contrast to the reports of Oliveira et al [35] and Santos et al [36], in this study, the number of dominant genes for PE was close to zero (−0.04 under WS and−0.08 under WW), demonstrating that there are no dominant alleles in the genes that control PE. Moreover, the determination coefficient in the narrow sense was >50%; therefore, the additive effect is predominant over the non-additive effects, regardless of the water regime [15,20].…”
Section: Additive and Dominance Effectscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the reports of Oliveira et al [35] and Santos et al [36], in this study, the number of dominant genes for PE was close to zero (−0.04 under WS and−0.08 under WW), demonstrating that there are no dominant alleles in the genes that control PE. Moreover, the determination coefficient in the narrow sense was >50%; therefore, the additive effect is predominant over the non-additive effects, regardless of the water regime [15,20].…”
Section: Additive and Dominance Effectscontrasting
confidence: 99%
“…However, in an evaluation of the same trait by SSR mapping, Babu et al [34] found QTLs with both dominant and partially dominant gene action. Similarly, in diallel studies on PE, Oliveira et al [35] and Santos et al [36] detected dominant gene action.…”
Section: Additive and Dominance Effectsmentioning
confidence: 87%
“…On the other hand, molecular marker studies identified markers associated with QTLs for popping expansion with complete dominance, partial dominance and overdominance effects (Babu et al, 2006;Li et al, 2017), clearly showing the non-exclusivity of additive effects on PE expression. More recently, Oliveira et al (2018) observed the influence of dominance effects on PE in a diallel analysis of S3 popcorn lines and recommended the exploitation of heterosis for significant increases in the trait. Moreover, in an attempt to better understand PE inheritance, Coan et al (2019) established the popcorn × dent corn cross and stated mixed inheritance in PE expression.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of increasing gains in popping expansion in intrapopulation breeding programs (Pacheco et al, 1998;Pereira and Amaral Júnior, 2001;Amaral Junior et al, 2013;Vieira et al, 2017;Guimarães et al, 2019), the existence of publications describing dominance effects for PE must lead to the recommendation of hybrid exploitation with a view to improving the popping expansion (Faria et al, 2008;Oliveira et al, 2018;Coan et al, 2019;Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to targeted breeding and selection, the PE capacity of popcorn has significantly increased over the last few decades. Recent reports have demonstrated that the PE values of popcorn have approximately doubled in comparison to those of the older American (25 mL.g -1 ) (Galvão et al, 2015) and Brazilian popcorn varieties (15 mL.g -1 ) (Zinsly and Machado, 1987), and the PE values of the current popcorn breeds are approximately 30 mL.g -1 (Amaral Junior et al, 2012;Oliveira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%